Reduction of hydroxy-functionalised carbaboranyl carboxylic acids and ketones by organolithium reagents. Issue 14 (11th March 2015) - Neumann, W.; Hiller, M.; Sárosi, M. B.; Lönnecke, P.; Hey-Hawkins, E.
Abstract : A hydroxyl group at the carbaborane cluster reduces exo -polyhedral C–C cleavage and enables reduction of carbaboranyl carboxylic acids and ketones to tertiary alcohols by organolithium reagents. Abstract : While the reaction of carbaboranyl carboxylic acids and ketones with organolithium reagents generally leads to cleavage of the exo -polyhedral C–C bond, introduction of a hydroxyl group at the second carbon atom of the cluster enables the reduction of the carbonyl compounds to tertiary alcohols. The proposed mechanism involving the formation of dimeric contact ion pairs was supported by X-ray crystallography and theoretical calculations.